Hybrid environmental-media facades: rationale and feasibility. (3rd September 2019) - Moloney, Jules; Globa, Anastasia; Wang, Rui; Khoo, Chin Koi; Tokede, Olubukola
ABSTRACT: It has been demonstrated that kinetic sunscreens linked to intelligent building systems have the potential to improve the energy performance of large-scale public and commercial buildings. However, there has been minimal uptake, primarily due to the capital and maintenance costs. This study proposes that costs can be offset through adding value by repurposing the sunscreening system as a low-resolution media screen. To evaluate the feasibility of this hybrid environmental-media facade concept, physical prototypes has developed and calibrated to real-time simulation and control software; and two case studies were undertaken to assess the physical and economic feasibility. This article introduces the rationale for a hybrid façade, documents the prototypes and case studies, and outlines further work on control systems for a truly smart building façade.